Pengembangan Taman untuk Meningkatkan Integrasi Lingkungan Hijau di Universitas Sunan Giri Surabaya - Nunik Hidayati; Miftakhul Jannah; Zhunnun Qothrunnada Annisa Salam Al-Madury; Rahayu Mardikaningsih; Didit Darrmawan; Rafadi Khan Khayru; Mila Hariani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The development of the park at Sunan Giri University Surabaya aims to improve the integration of the green environment on campus through the utilization of ecological, social, cultural, economic, and aesthetic functions of the park as a green open space. This research uses the Asset-Based Community Development (ABCD) method to develop the park as a green space at Sunan Giri University Surabaya. The ABCD method focuses on utilizing community assets, such as available land and the support of the academic community, to design parks that function ecologically, aesthetically, socially, and economically. Through observation and focus group discussions, community needs and potentials were identified for garden planning. Project implementation was carried out in stages involving active participation from the campus community. The results showed that the developed garden successfully improved the aesthetics and tidiness of the campus environment and supported social and cultural functions. The evaluation showed that the success of the program was influenced by community support and land availability, despite challenges such as dry soil conditions. The development of this garden is expected to become a model of environmental sustainability and strengthen the university's image as an institution that cares about the environment.